Konfrontacja różnych pamięci w przestrzeni scenicznej na przykładzie spektakli biograficznych z Teatru Śląskiego (Leni Riefenstahl. Epizody niepamięci i What the heil?!) (Politeja, 2023)
CONFRONTING DIVERSE MEMORIES ON STAGE: BIOGRAPHICAL PLAY AT THE SILESIAN THEATRE IN KATOWICE (LENI RIEFENSTAHL. EPIZODY NIEPAMIĘCI AND WHAT THE HEIL?!)In recent Polish theater, numerous projects have drawn inspiration from biographies. These practices not only reflect the prevailing biographical trend in culture but also indicate that theater serves as a “memory machine,” playing a socially important role in establishing connections between the past and the present. Drawing on the examples of two plays staged at the Silesian Theatre in Katowice, namely Leni Riefenstahl. Epizody niepamięci [Leni Riefenstahl. Episodes of Non-memory] (2016) and What the heil?! (2022), and employing the concepts of cultural memory (A. Assmann, J. Assmann), postmemory (M. Hirsch) and multidirectional memory (M. Rothberg), this study examines the conventions employed in r e c o n s t r u c t i n g t h e p a s t wi t h i n t h e th e at r i c a l spa c e . Furthermore, it delves into t h e dynami c s o f va r i - o u s f o rms o f memo r y (e.g. cultural memory, communicative memory, individual memory) in theatrical representation.